Single agent vemurafenib or rituximab-vemurafenib combination for the treatment of relapsed/refractory hairy cell leukemia, a multicenter experience - Yiğit Kaya, Süreyya; Mutlu, Yaşa Gül; Malkan, Ümit Yavuz; Mehtap, Özgür; Keklik Karadağ, Fatma; Korkmaz, Gülten; Elverdi, Tuğrul; Saydam, Güray; Özet, Gülsüm; Ar, Muhlis Cem; Melek, Elif; Maral, Senem; et al. (My University, 2024)
Background: Hairy cell leukemia (HCL) is a rare mature B-cell malignancy that is primarily treated with purine analogues. However, relapse remains a significant challenge, prompting the search for alternative therapies. The BRAF V600E mutation prevalent in HCL patients provides a target for treatment with vemurafenib. Patients and methods: This multicenter retrospective study included nine patients with relapsed/refractory (R/R) HCL from six different centers. Patient data included demographics, prior treatments, clinical outcomes, and adverse events. Results: Patients received different treatment regimens between centers, including vemurafenib alone or in combination with rituximab. Despite the differences in protocols, all patients achieved at least a partial response, with seven patients achieving a complete response. Adverse events were generally mild with manageable side effects. The absence of myelotoxic effects and manageable side effects make BRAF inhibitors attractive, especially for patients ineligible for purine analogues or those with severe neutropenia. Conclusion: Single agent vemurafenib or in combination with rituximab appears to be a promising therapeutic option for R/R HCL. Further research is needed to establish standardized treatment protocols and to investigate long-term outcomes.
Keywords: BRAF Inhibitor; Hairy Cell Leukemia; Rituximab; Vemurafenib